Acquisition Duration in Resting-State Arterial Spin Labeling. How Long Is Enough? - Vallée, Corentin; Maurel, Pierre; Corouge, Isabelle; Barillot, Christian (Frontiers in Neuroscience, 2020)
Resting-state Arterial Spin Labeling (rs-ASL) is a rather confidential method compared to resting-state BOLD but drives great prospects with respect to potential clinical applications. By enabling the study of CBF maps, rs-ASL can lead to significant clinical subject-scaled applications as CBF is a biomarker in neuropathology. An important parameter to consider in functional imaging is the acquisition duration. Despite directly impacting practicability and functional networks representation, there is no standard for rs-ASL. Our work here focuses on strengthening the confidence in ASL as a rs-fMRI method and on studying the influence of the acquisition duration. To this end, we acquired a long rs-ASL sequence and assessed the quality of typical functional brain networks quality over time compared to gold-standard networks. Our results show that after 14 min of duration acquisition, functional networks representation can be considered as stable.